The Contribution of Direct Hands-On Instruction Relative to Indirect One on Primary Students' Achievement in Science - Stanko M. Cvjetićanin; Mirjana T. Maričić (University of Belgrade, Teacher Education Faculty, 2022)
Ensuring the optimal (adequate) level of instructional guidance in teaching natural sciences in primary education is of utmost importance for the proper acquisition and application of knowledge. The goal of this paper is to examine the contribution of direct hands-on instruction relative to an indirect one on student achievement regarding the movement and properties of materials in classes of integrated natural sciences (classes of the World around Us and Science and Social Studies). The research tasks include a comparative analysis of the quality of students' knowledge acquired with the application of direct in relation to indirect hands-on instruction, as well as the analysis of the permanence of that knowledge. The following methods were used in the research: theoretical analysis method, descriptive-analytical method, and experimental method. The research technique is testing, and the instrument is knowledge tests (pre-test, post-test, and re-test). The research sample consisted of 94 students of the third grade of primary school, divided into two groups: E1 (application of indirect hands-on instruction) and E2 group (application of direct hands-on instruction). The results of the research indicate that the students of the E1 group achieved somewhat better and more lasting knowledge about the movement and properties of materials in relation to the students of the E2 group. However, a significant difference between their achievements was observed only at the cognitive level evaluated in the post-test. This leads to the conclusion that both types of hands-on instructions should be applied in the third grade when teaching the content related to the movement and properties of materials. In addition, greater preference should be given to indirect over direct hands-on instruction because it not only provides an opportunity for students to have better achievement, but also it enables a greater degree of independent research and experimental work.